STUDI GEOLOGI DAN GEOFISIKA POTENSI HIDROKARBON FORMASI AIR BENAKAT LAPANGAN X CEKUNGAN SUMATERA SELATAN - Simorangkir, Fenry; Haryanto, Iyan; -, Nurdrajat; Firmansyah, Yusi (Bulletin of Scientific Contribution, 2015)
X field is part of the South Sumatra Basin with an area of 359,6 km2. This study is focused to discuss potential hydrocarbons in x fiels. In this study, the discussion will be focused on the Air Benakat Formation. The method used is based on the interpretation of seismic and well. Based on the results of the analysis of the petrophysic of the FS, HA, and BS well shows average Netpay on Air Benakat Formation is 180 m, with a cut-off Volume Shale 0.4, cut-off PHIE 0.12 and cut-off Saturation Water 0.71. As for the Netpay from reservoir itself is average 12.415 m. Geological modeling based on the results obtained by petroleum leads three zone with two reservoir zones. For reservoar A, the most potentially zone is the zone of Lead-1 with with a resources amount of 716.82 MMBO, Zone of Lead-2 with a resources amount of 398.89 MMBO, and zone of Lead-3 with a resources amount of 108.14 MMBO. For resevoar B, the most potentially zone is the zone of Lead-1 with a resources amount of 662.13 MMBO, Lead-2 Zone with a total resources of 368.46 MMBO, and zone of Lead-3 with a total resources of 99.89 MMBO.